Desabusadas e levadas do diabo: mulheres pobres no ambiente urbano de Santa Maria no início do século XX (1903-1918) - Santos, Gabriela Rotilli dos (2021)
In recent years, studies and researches dedicated to reflecting the daily life and experiences of the poor population have not only grown, but also elaborated their analyzes from sources not yet explored by historiography to think about these subjects. In this sense, this work financed with a CAPES/DS grant, inserted in the Culture, Migration and Work research line, is dedicated to the elaboration of social profiles and the experiences of poor women in the urban environment of the city of Santa Maria, located in the interior of the region. the center of the state of Rio Grande do Sul, in the early years of the 20th century (1903-19018). This construction will take place through documentation related to health, such as the Patient Entry Records of the Hospital de Charidade de Santa Maria, and to justice, such as criminal proceedings. The context in which the women studied by us traced their trajectories refers to the post-abolition period, where in the last years of the empire and in the first decades of the Brazilian Republic a sort of transformation manifested itself, whether related to the geographies of cities by the works of modernization guided by a hygienist urbanism as well as at the level of daily life, where the forms of population control were reorganized, and the resurgence of the persecution of the popular classes was expressed. The different conditions of access to equality and citizenship to which men and women egressed from captivity, as well as their descendants, were exposed, adds to the urban inability to absorb the huge contingent of workers now available. The intensification of the stimulus to European immigration not only adds more and more people to the streets of cities, but also fuels animosities that reflect the deep social racialization, as well as the harm and mitigation that social markers such as sex, color, class and nationality generate in the sense of access to affection, the city, jobs and health at this time. Through a micro-historical, serial and intersectional analysis, we seek to pay attention to the differences and specificities that constitute the studied women.